Nanoarchitectonics of Biofunctionalized Hydrogen‐Terminated 2D‐Germanane Heterostructures as Highly Sensitive Biorecognition Transducers: The Case Study of Cocaine Drug - Yiming Lei; Ángel Campos‐Lendínez; Xavier Sala; Jordi García‐Antón; Jose Muñoz (Small Structures)
Hydrogen‐terminated 2D‐germanane (2D‐GeH), as one inorganic 2D material akin to graphene, is attracting widespread interest owing to its predicted (opto)electronic properties. Nonetheless, the chemical reactivity of 2D‐GeH requires further exploration to expand its real implementation. Herein, a simple and straightforward bottom‐up biofunctionalization approach is reported aiming at providing the bases toward the robust design of 2D‐GeH‐based biorecognition systems with electrical readout. For this goal, 2D‐GeH has been firstly functionalized with gold nanoparticles (Au‐NPs) via an organometallic approach, followed by the covalent immobilization of a thiolated single‐stranded DNA (ssDNA) aptamer via AuS bond interactions. After an accurate material characterization, the resulting ssDNA/Au@GeH heterostructure is drop‐casted on a fluorine‐doped tin oxide (FTO) electrode for impedimetrically monitoring cocaine as a model drug. Interestingly, the aptamer–cocaine interactions hinder the interfacial electron‐transfer process of the benchmark [Fe(CN)6]3−/4− redox marker with increasing concentration of the cocaine target, leading to a detection limit as low as 4.9 ± 0.1 aM, the lowest one reported in literature by far. Overall, the ssDNA/Au@GeH electrochemical biosensor exhibits outstanding selectivity, specificity, and reproducibility, demonstrating the potential use of 2D‐GeH as an emerging highly sensitive transducer for biosensing applications. The reported method is general and might be simply customized by tailoring the biorecognition component.